Diameter effect on supercritical heat transfer - Yildiz, S.; Groeneveld, D. C. (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
The objective of this review is to assess and analyze the literature on the effect of tube diameter on heat transfer at super-critical (SC) pressures. The review is based on SC heat transfer data obtained in tubes with a diameter range of 3.18 to 38.1 mm, cooled by carbon dioxide, water, R-22, and R-12. The majority of experimental studies show that, for the same flow conditions, the heat transfer coefficient (HTC) in the 'normal' heat transfer mode increases with a decrease in tube diameter. Furthermore, it was found that at SC pressures, heat transfer is more prone to deteriorate in large tube diameters. In the deteriorated heat transfer mode, the HTC also appears to decrease with an increase in tube diameter. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Diameter effect; Super critical heat transfer; Deterioration; Thermodynamics; Mechanics